Immunological axis of berberine in managing inflammation underlying chronic respiratory inflammatory diseases. (1st February 2020) - Tew, Xin Nee; Xin Lau, Natalie Jia; Chellappan, Dinesh Kumar; Madheswaran, Thiagarajan; Zeeshan, Farrukh; Tambuwala, Murtaza M.; Aljabali, Alaa AA.; Balusamy, Sri Renukadevi; Perumalsamy, Haribalan; Gupta, Gaurav; Oliver, Brian G.; Hsu, Alan; et al.
Abstract: Inflammatory responses play a remarkable role in the mechanisms of acute and chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD), asthma, pulmonary fibrosis and lung cancer. Currently, there is a resurgence in the use of drugs from natural sources for various ailments as potent therapeutics. Berberine, an alkaloid prominent in the Chinese traditional system of medicine has been reported to exert therapeutic properties in various diseases. Nevertheless, the number of studies focusing on the curative potential of berberine in inflammatory diseases involving the respiratory system is limited. In this review, we have attempted to discuss the reported anti-inflammatory properties of berberine that function through several pathways such as, the NF-κB, ERK1/2 and p38 MAPK pathways which affect several pro-inflammatory cytokines in the pathophysiological processes involved in chronic respiratory diseases. This review would serve to provide valuable information to researchers who work in this field and a new direction in the field of drug discovery with respect to respiratory diseases. Highlights: Inflammatory responses play a crucial role in chronic respiratory diseases. Berberine functions through the NF-kB, ERK1/2 and p38 MAPK pathways. Berberine causes a decrease in pro-inflammatory cytokine levels. Berberine improves the histological changes in the lung tissue of rat models. Berberine suppresses tumours by increasing the activity of FOXO3a.